Subchronic exposure to 1,2-naphthoquinone induces adipose tissue inflammation and changes the energy homeostasis of mice, partially due to TNFR1 and TLR4 - Oliveira Ferreira, Clílton Kraüss de; Campolim, Clara Machado; Zordão, Olívia Pizetta; Simabuco, Fernando Moreira; Anaruma, Chadi Pellegrini [UNESP]; Pereira, Rodrigo Martins; Boico, Vitor Ferreira; Salvino, Luiz Guilherme; Costa, Maíra Maftoum; Ruiz, Nathalia Quintero; de Moura, Leandro Pereira [UNESP]; Saad, Mario Jose Abdalla; et al. (Elsevier, 2023)
Air pollution affects energy homeostasis detrimentally. Yet, knowledge of how each isolated pollutant can impact energy metabolism remains incomplete. The present study was designed to investigate the distinct effects of 1,2-naphthoquinone (1,2-NQ) on energy metabolism since this pollutant increases at the same rate as diesel combustion. In particular, we aimed to determine in vivo effects of subchronic exposure to 1,2-NQ on metabolic and inflammatory parameters of wild-type mice (WT) and to explore the involvement of tumor necrosis factor receptor 1 (TNFR1) and toll-like receptor 4 (TLR4) in this process. Males WT, TNFR1KO, and TLR4KO mice at eight weeks of age received 1,2-NQ or vehicle via nebulization five days a week for 17 weeks. In WT mice, 1,2-NQ slightly decreased the body mass compared to vehicle-WT. This effect was likely due to a mild food intake reduction and increased energy expenditure (EE) observed after six weeks of exposure. After nine weeks of exposure, we observed higher fasting blood glucose and impaired glucose tolerance, whereas insulin sensitivity was slightly improved compared to vehicle-WT. After 17 weeks of 1,2-NQ exposure, WT mice displayed an increased percentage of M1 and a decreased (p = 0.057) percentage of M2 macrophages in adipose tissue. The deletion of TNFR1 and TLR4 abolished most of the metabolic impacts caused by 1,2-NQ exposure, except for the EE and insulin sensitivity, which remained high in these mice under 1,2-NQ exposure. Our study demonstrates for the first time that subchronic exposure to 1,2-NQ affects energy metabolism in vivo. Although 1,2-NQ increased EE and slightly reduced feeding and body mass, the WT mice displayed higher inflammation in adipose tissue and impaired fasting blood glucose and glucose tolerance. Thus, in vivo subchronic exposure to 1,2-NQ is harmful, and TNFR1 and TLR4 are partially involved in these outcomes.
Keywords: 1; 2-naphthoquinone; Air pollution; Diesel; Energy balance; Inflammation; Macrophages; PM2.5; White adipose tissue